Peter Watson. The Age of Nothing: How We Have Sought to Live Since the Death of God. - Solovij, Roman Pavlovyč (Bogoslovskie razmyšlenija, 2018)
Book reviwe: Epokha pustoty. Kak liudi nachali zhit’ bez Boga, chem zamenili religiiu i chto iz vsego etogo vyshlo [The Age of Nothing: How We Have Sought to Live Since the Death of God]. By Peter Watson. Trans. from English by M. Zavalov, N. Kholmogorovaia. (Series: Religion. The History of God). Moscow: Eksmo, 2017. Пер. с англ. М. Завалова, Н. Холмогоровой (Серия: Религия. История Бога). Pp. 784; ISBN 978-5-699-97046-9; 738 RUB.